Bridging self-directed learning and competency in interdisciplinary teaching among STEM lecturers: How psychological capital connects - Wenhao Su; Hidayah Mohd Fadzil; Rose Amnah Abd. Rauf (PLoS ONE, 2025)
University STEM education is vital for cultivating innovative talents but is hindered by a lack of lecturers skilled in interdisciplinary teaching. Research on the interplay between psychological capital (PsyCap), competency in interdisciplinary teaching (CIT), and self-directed learning (SDL) is limited. This study investigates a mediation model, exploring PsyCap’s role between SDL and CIT among 427 Chinese STEM lecturers using proportional stratified random sampling and partial least squares structural equation modeling (PLS-SEM). The results revealed that SDL had a significant direct effect on CIT (β = 0.210, t = 4.429, p < 0.001) and PsyCap (β = 0.603, t = 16.737, p < 0.001). PsyCap also significantly influenced CIT (β = 0.546, t = 12.748, p < 0.001). Mediation analysis further indicated that PsyCap partially mediated the relationship between SDL and CIT, with a significant indirect effect (β = 0.329, t = 9.738, p < 0.001). These findings contribute to the literature by validating a novel mediation model integrating SDL and PsyCap to explain CIT. It also offers practical implications for offering practical pathways for improving the training of STEM lecturers, with SDL and PsyCap identified as key leverage points for enhancing the quality of interdisciplinary teaching in universities. Given the study’s single-mediator design, future research may adopt moderated mediation models to explore when and how SDL and PsyCap more strongly influence interdisciplinary teaching competency.